Harmonization of customary and Islamic law in the gama tradition of the muslim Mongondow community of North Sulawesi - Rosdalina Bukido; Nurlaila Harun; Edi Gunawan; Rahman Mantu (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2022)
Gama in the Mongondow Muslim community is considered mandatory to determine a marriage’s validity. Therefore, this study aims to examine in depth the relevance of customary and Islamic law to the tradition of gama in the Muslim community of Mongondow, North Sulawesi. The study was conducted in the Bolaang Mongondow area of North Sulawesi using a juridical-sociological approach. Data were collected using observation, interviews with traditional and religious leaders, as well as document study. The steps in data processing include data collection, presentation, reduction, and verification. Furthermore, analysis was carried out using the concept of urf and receptie a contrario. The results showed that even though the gama tradition predates the arrival of Islam in Bolaang Mongondow area, its implementation has Islamic values, otherwise known as urf shahih. The community upholds the noble values of traditions passed down by their ancestors. Islam teaches that the gama tradition has a symbol of respect for women. This indicates that customary and Islamic law play a joint role in shaping the life of the Bolaang Mongondow people. Conclusively, respect for the existence of women is a noble value in the Customary law of the Mongondow people.